Pengembangan Media Komik Digital Berbasis Kearifan Lokal untuk Meningkatkan Minat Belajar Peserta Didik dan Keterampilan Berpikir Kritis pada Pembelajaran Bahasa Indonesia di Kelas 5 SD - Lestari, Ayu; Muhtarom, Muhtarom; Ngatmini, Ngatmini (Universitas PGRI Semarang, 2025)
The background of the problem faced by the researcher is the lack of interest in learning and critical thinking skills of students in Indonesian language lessons. This is indicated by the results of the researcher’s observation by distributing a questionnaire in Class V of SDN Jragung 2 on February 12, 2024. The teacher has used learning media but has still not been able to improve students' interest in learning and critical thinking skills. The purpose of this research is to determine the practicality of Digital Comic Media Based on Local Wisdom to enhance students' interest in learning and critical thinking skills in Indonesian language learning in grade 5 elementary school and to determine the effectiveness of digital comic learning media based on local wisdom in improving critical thinking skills of fifth-grade students in Indonesian language learning. The approach used by the researcher is research and development (RnD) the research design used is the Borg and Gall model where the researcher only takes 7 steps, namely, information collection, planning, initial product development, initial trial, product revision, field trial, product registration. The research will be carried out in grade 5 at SD Negeri Jragung 2, Karangawen district in semester 2 with a total of 31 students. Data collection techniques use observation, interviews and questionnaires. Data analysis techniques are validation tests, practicality tests, normality tests, homogeneity tests, and T tests. The results of research on the development of digital comic media based on local wisdom have been proven to be valid, effective, and practical to increase the interest in learning and critical thinking skills of 5th grade elementary school students.